An analysis of the West Java governor's policy on vasectomy as a requirement for receiving social assistance from the perspective of mashlahah mursalah - Irwan Syah; Arsal Arsal (LP3M Universitas Islam Zainul Hasan Genggong, 2026)
The main issue discussed in this journal article concerns the proposal of the Governor of West Java to link Family Planning (KB) programs with social assistance by requiring vasectomy for families with many children. This policy is based on the assumption that having a large number of children exacerbates poverty, making birth control an important instrument for regional economic development. This study explains the development of the concept and regulations of social assistance in Indonesia, evaluates the rationality of the West Java Provincial Government’s vasectomy requirement policy, and examines its compatibility with the principle of maslahah mursalah in poverty alleviation. The research employs a library research method, relying on secondary data obtained from various academic sources, including books, scholarly articles, and other relevant documents. The findings indicate that social assistance programs in Indonesia have evolved since the New Order era and became more prominent during the administration of President Susilo Bambang Yudhoyono, with eligibility generally limited to poor or vulnerable Indonesian citizens registered in the Integrated Social Welfare Data System (DTKS). The high poverty rate and low participation in vasectomy programs in West Java have encouraged Dedi Mulyadi to propose vasectomy as a requirement for receiving social assistance. From the perspective of maslahah mursalah, this policy can be viewed as an effort to promote public welfare through improving family well-being, enhancing public health, and reducing poverty, while still upholding the principles of justice and the rights of citizens. Ultimately, the welfare of society should remain the primary objective in the formulation and implementation of every social policy.